2019
DOI: 10.14569/ijacsa.2019.0100137
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Gateway-based Context-Aware and Self-Adaptive Security Management Model for IoT-based eHealth Systems

Abstract: IoT-based systems have considerable dynamic behavior and heterogeneous technology participants. The corresponding threats and security operations are also complex to handle. Traditional security solutions may not be appropriate and effective in such ecosystems as they recognize and assess a limited context, they work well only with high-end and specific computing platforms, and implement manual response mechanisms. We have identified the security objectives of a potential IoT-eHealth system and have proposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Many researchers in the last decade have addressed the literature concerning IoT privacy and security. It has been observed that addressing the security issues was primarily focused [11]; however, more attention needs to be paid to the protection of end-user privacy in modern electronic health care systems [12], [13]. In the modern era, the health care system is transformed into a new domain by incorporating advanced digital technologies such as IoT, high computing devices to store and process data, personal health records, and more.…”
Section: Security and Privacy Of Iomtmentioning
confidence: 99%
“…Many researchers in the last decade have addressed the literature concerning IoT privacy and security. It has been observed that addressing the security issues was primarily focused [11]; however, more attention needs to be paid to the protection of end-user privacy in modern electronic health care systems [12], [13]. In the modern era, the health care system is transformed into a new domain by incorporating advanced digital technologies such as IoT, high computing devices to store and process data, personal health records, and more.…”
Section: Security and Privacy Of Iomtmentioning
confidence: 99%
“…1) The adaptation process: The adaption process in an adaptive S&P system can be typically divided into three main functionalities or phases [8,13,16,17]: Monitoring, Analysis, and Adaptation. They enable a system to adapt the S&P configurations based on the dynamic changes in the IoT ehealth infrastructure in an automated manner.…”
Section: B the Proposed Assessment Frameworkmentioning
confidence: 99%
“…Monitoring also observe external factors such as those related to the monitored devices, users, network and applications. Therefore, it attempts to collect data essential for a context-aware analysis and adaptation [8,16,17].…”
Section: B the Proposed Assessment Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Context-aware solutions for multimodal data compression, in-network processing, and edge-event detection in multi-edge cloud-based systems [56] are promising. A context-aware and self-adaptive model serving as an IoT security management platform that can autonomously track, interpret, and respond to a host of security contexts are proposed in [124] . That model harnesses the benefits of fog computing and provides flexibility and open networking to handle any smart device.…”
Section: Smart and Connected Health: Review Classification And Comparisonmentioning
confidence: 99%